Non-invasive T1ρ mapping of the human cartilage response to loading and unloading. Issue 2 (February 2018) - Nebelung, S.; Sondern, B.; Jahr, H.; Tingart, M.; Knobe, M.; Thüring, J.; Kuhl, C.; Truhn, D.
Summary: Objective: To define the physiological response to sequential loading and unloading in histologically intact human articular cartilage using serial T1ρ mapping, as T1ρ is considered to indicate the tissue's macromolecular content. Method: 18 macroscopically intact cartilage-bone samples were obtained from the central lateral femoral condyles of 18 patients undergoing total knee replacement. Serial T1ρ mapping was performed on a clinical 3.0-T MRI system using a modified prostate coil. Spin-lock multiple gradient-echo sequences prior to, during and after standardized indentation loading (displacement controlled, strain 20%) were used to obtain seven serial T1ρ maps: unloaded (δ0 ), quasi-statically loaded (indentation1 –indentation3 ) and under subsequent relaxation (relaxation1 –relaxation3 ). After manual segmentation, zonal and regional regions-of-interest were defined. ROI-specific relative changes were calculated and statistically assessed using paired t -tests. Histological (Mankin classification) and biomechanical (unconfined compression) evaluations served as references. Results: All samples were histologically and biomechanically grossly intact (Mankin sum: 1.8 ± 1.2; Young's Modulus: 0.7 ± 0.4 MPa). Upon loading, T1ρ consistently increased throughout the entire sample thickness, primarily subpistonally (indentation1 [M ± SD]: 9.5 ± 7.8% [sub-pistonal area, SPA] vs 4.2 ± 5.8% [peri-pistonal area, PPA]; P < 0.001). T1ρ further increased with ongoing loading (indentation3 : 14.1 ± 8.1 [SPA] vs 7.7 ± 5.9% [PPA]; P < 0.001). Even upon unloading (i.e., relaxation), T1ρ persistently increased in time. Conclusion: Serial T1ρ-mapping reveals distinct and complex zonal and regional changes in articular cartilage as a function of loading and unloading. Thereby, longitudinal adaptive processes in hyaline cartilage become evident, which may be used for the tissue's non-invasive functional characterization by T1ρ.